ผลกระทบของอิเลกโตรไลต์ต่างชนิดในแบตเตอรี่สังกะสีไอออน - ชยุต ทัศนโพธิ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2019)
Zn-ion batteries are one of the most actively developing rechargeable batteries that are alternatives to Li-ion batteries. It is due to their low cost and high safety. Many researches have been conducted to develop Zn-ion batteries so as to increase their performance. However, fundamental understanding of the transport mechanisms of Zn ion (Zn²⁺) in electrolytes that affect conductivity, subsequently in performance is not wellestablished. The aim of this study is to elucidate structure and dynamic properties of Zn²⁺ in different electrolytes using molecular dynamics simulation. Effects of concentration [zinc sulfate (ZnSO₄) at 0.1, 0.5, 1, 2 and 3 M] and electrolyte types [ZnSO₄, zinc trifluoromethylsulfonate (Zn(OTf) ₂) and zinc chloride (ZnCl₂) at 1 M] on structure and dynamic properties of Zn²⁺ were investigated. When the concentration of ZnSO₄ increased, the diffusion coefficient of Zn²⁺ decreased. This is because the number of ions in aqueous solution increased, causing dense system, and thus diffusion of Zn²⁺ was limited. It was also found the agglomeration of ions at very high concentrations, i.e., at 2 M and 3 M. When the electrolyte size increased, i.e., the system of Zn(OTf) ₂, the diffusion coefficient of Zn²⁺ decreased. The results obtained provide fundamental understanding of the role of electrolyte diffusion, perhaps provide guideline for designing Zn-ion battery system.